The Digital Entrepreneurship Era: How to Motivate Innovativeness in Middle Management Teams? The Vertical Organisational Pervasiveness of Chief Executive Officer Entrepreneurial Orientation - Zhang, Xu; Liu, Yueyue; Geng, Xiulin; Wei, Danxia (Frontiers in Psychology, 2022)
Social information processing theory suggests that the CEO’s entrepreneurial orientation (CEO EO) is an organisational signal that influences the members’ innovativeness. Middle management teams (MMTs) are expected to be more innovative as they connect senior managers with frontline managers in the dynamic competitive environment of the digital economy. How CEOs guide MMT innovations through EO becomes critical in the process of capturing opportunities and creating value. However, previous research has failed to adequately identify distinct CEO EO manifestations with organisational contexts configurations that influence MMTs innovation. Thus, based on differences in organizational contexts and MMTs' cognition, this study thoroughly investigates how the vertical manifestation of CEO EO impacts the innovativeness of MMTs. We used fuzzy-set qualitative comparative analysis (fsQCA) on a sample of 117 organizations to determine which configurations of CEO EO vertical penetration within an organization can stimulate MMT innovativeness. The study discovered four first-level configurations that support stimulating MMT innovativeness respectively when the CEO EO is fully or partially manifested, and without the CEO EO. Moreover, we found the internal reasons for MMTs' information interpretation heterogeneity, which is critical for realising the coordination and unity of entrepreneurial cognition and behaviours. Finally, these findings' theoretical and practical implications are discussed.